New linear antiplasmodial peptides related to angiotensin II. (December 2015) - Silva, Adriana; Torres, Marcelo Der; Silva, Leandro de; Alves, Flávio; Pinheiro, Ana; Miranda, Antonio; Capurro, Margareth; Oliveira, Vani
Abstract Background Antiplasmodial activities of angiotensin II and its analogues have been extensively investigated inPlasmodium gallinaceum andPlasmodium falciparum parasite species. Due to its vasoconstrictor property angiotensin II cannot be used as an anti-malarial drug. Methods This work presents the solid-phase syntheses and liquid chromatography and mass spectrometry characterization of ten linear peptides related to angiotensin II against matureP. gallinaceum sporozoites and erythrocyte invasion byP. falciparum . Conformational analyses were performed by circular dichroism. IC50 assays were performed to identify the ideal concentration used on the biological tests and haemolytical erythrocytic assays were made to verify the viability of the biological experiments. The contractile responses of the analogues were made to evaluate if they are promising candidates to be applied as antiplasmodial drugs. Results The results indicate two short-peptides constituted by hydrophobic residues (5 and 6) with antiplasmodial activity in these models, 89 and 94 % of biological activity againstP. gallinaceum sporozoite, respectively, and around 50 % of activity againstP. falciparum . Circular dichroism spectra suggested that all the peptides adopted β-turn conformation in different solutions, except peptide 3. Besides the biological assays IC50, the haemolysis assays and contractile response activities were applied for peptides 5 and 6, which did not present expressive results. Conclusions The hydrophobic portion and the arginine, tyrosine, proline, and phenylalanine, when present on peptide primary sequence, tend to increase the antiplasmodial activity. This class of peptides can be explored, as anti-malarial drugs, after in vivo model tests.Graphical abstract: The most active peptide presented 94 % activity onP. gallinaceum sporozoites and 53 % inhibitedP. falciparum ring forms invasion